2017
DOI: 10.1097/hjh.0000000000001173
|View full text |Cite
|
Sign up to set email alerts
|

Time to the peak of the aortic forward wave determines the impact of aortic backward wave and pulse pressure on left ventricular mass

Abstract: Time to the peak of the aortic forward wave, but not early wave reflection markedly influences the impact of aortic backward wave pressure and hence aortic pulse pressure on LVMI and LVH in adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The use of the pressureblood flow ''triangulation method'' of aortic wave separation to derive aortic Pf and Pb has been largely employed and shown adequate reproducibility and clinical value. Tade et al showed similar relations between Pf or Pb and cardiovascular remodeling when Pb or Pf was derived from WSA employing pressure and blood flow measurements versus Pb or Pf derived from the triangular waveform approach to WSA [32]. Our work has the limitation of being a crosssectional design.…”
Section: Limitationsmentioning
confidence: 84%
“…The use of the pressureblood flow ''triangulation method'' of aortic wave separation to derive aortic Pf and Pb has been largely employed and shown adequate reproducibility and clinical value. Tade et al showed similar relations between Pf or Pb and cardiovascular remodeling when Pb or Pf was derived from WSA employing pressure and blood flow measurements versus Pb or Pf derived from the triangular waveform approach to WSA [32]. Our work has the limitation of being a crosssectional design.…”
Section: Limitationsmentioning
confidence: 84%
“…AIx offers some insight into global wave reflection magnitude in type A waveforms where there is a clear augmentation of pressure at the inflection point/ascending shoulder. However, as eloquently discussed by Mitchell 61, when AIx is > 0, augmented pressure from the pressure waveform alone represents just the "tip of the iceberg" because the majority of the reflected wave may be masked by the falling edge of the forward pressure wave (62,63). In children with Type C waveforms (negligible/no augmentation of pressure above the shoulder), AIx may not capture wave reflection magnitude because calculated values are negative (P 2 < P 1 ).…”
Section: Racial Differences In Central Hemodynamic Loadmentioning
confidence: 99%
“… 9 Moreover, the times to pressure peak of forward (T for ) and reflected (T ref ) waves were associated with higher risk groups in cross-sectional studies. 15 , 16 Although premature wave reflections were associated with outcomes in patients with heart failure with a reduced ejection fraction, 17 whether T for and T ref are predictive of cardiovascular end points in general populations is not known.…”
mentioning
confidence: 99%